STRATEGI GURU PENDIDIKAN AGAM ISLAM DALAM MEMBENTUK SSA (SPIRITUAL AND SOCIAL ATTITUDE) PESERTA DIDIK PADA MASA PANDEMI COVID-19 DI SMA NEGERI 1 - Fatma Fatma; Abdul Jalil; Qurroti A’yun (VICRATINA, 2022)
This research is a type of case study research. This study aims to describe and analyze phenomena, events, social activities, and attitudes. The main purpose of this research is to develop and form a strategy for Islamic religious education teachers in forming SSA (spiritual and social attitude) for students during the COVID-19 pandemic. The specific purpose of this research is to find out how to develop and shape the spiritual and social attitudes of students during the current pandemic. The formation of spiritual attitudes and social attitudes is carried out by Islamic religious education teachers themselves. Data collection techniques used by interviews, observation, and documentation. Qualitative data were analyzed using a ratio scale. This study resulted in the strategy of Islamic religious education teachers in forming SSA (spiritual and social attitude) students during the COVID-19 pandemic "this strategy uses habituation, classical approach modeling, individual approach, parent approach, caramah method, discussion, question and answer, and assignment g,. Based on the validation that has been carried out by material experts and Islamic religious education teachers, on average, they have reached the target. Thus, it can be concluded that the strategy of Islamic religious education teachers in forming SSA (spiritual and social attitude) for students during the COID-19 pandemic made by researchers is suitable for use in learning spiritual attitudes and social attitudes.